The automatic termination of employment contract and its effect in South Africa - Rammai, Kamogelo Makgabo (My University, 2024)
The study will analyse the legal position of the automatic termination of employment contract and the consequences associated with it on both the employer and the employees. The study outlines events which lead to employment contracts terminating without a need of the either party informing the other. The study covered circumstances which can lead to the automatic termination of employment contract amounting to unfair dismissal. The study will further make a brief comparison with the labour law position relating to automatic termination of employment contract in the United Kingdom (“UK”). At the end, the study provides recommendations on how the automatic termination of employment contract may be invoked or carried out without the employer unfairly dismissing or committing unfair labour practices against the employees.
Thesis (LLM. (Labour Law)) -- University of Limpopo, 2024
Keywords: Employment contracts; Automatic termination; Labour law; Contracts; Labor contract -- South Africa; Employees -- Dismissal of